The Importance of Customer Relationship Management in the Automotive Market - Adrian-Costinel Tănase (Robotica & Management)
The complexity of economic life is the essential cause of the need to know the mechanism of consumer behaviour. Communication with customers is a vital aspect for the success of a company, regardless of the market in which it operates. Customer Relationship Management and relationship marketing are interconnected concepts and refer to the management of an organization’s “partnership” with its customers, but they are also different concepts. This paper aims to present the importance of customer relationship management in the automotive market.